LEFT—A web‐based tool for the remote measurement and estimation of ecological value across global landscapes. Issue 3 (26th December 2017) - Long, Peter R.; Benz, David; Martin, Andrew C.; Holland, Philip W. A.; Macias‐Fauria, Marc; Seddon, Alistair W. R.; Hagemann, Randi; Frost, Tone K.; Simpson, Andrew; Power, David J.; Slaymaker, Mark A.; Willis, Kathy J.
Abstract: The overall aim in the development of the Local Ecological Footprinting Tool (LEFT) was to design a web‐based tool that could provide quickly obtained quantitative data on ecological risk to assist landowners when making land‐use change decisions. The Local Ecological Footprinting Tool works for almost any region in the world and uses freely available satellite imagery, biotic and abiotic data from existing global databases, models and algorithms to deliver a customised report for a selected area within one hour of job submission. Biotic data automatically obtained for a selected landscape includes terrestrial vertebrate and plant species occurrence data, information on their conservation status and remotely sensed vegetation productivity. Abiotic information obtained includes temperature, precipitation, water availability, insolation, topography, elevation, distribution of urban infrastructure and location of wetlands. The tool performs a number of analyses on the biotic and abiotic data to produce maps for the selected area at a 30 m resolution depicting land cover type, numbers of globally threatened terrestrial vertebrate and plant species, beta‐diversity of terrestrial vertebrates and plants, habitat intactness, wetland habitat connectivity, numbers of migratory species and vegetation resilience. Results are also aggregated to produce a summary map demonstrating areas of high and low ecological risk across the selected area. The Local Ecological Footprinting Tool has been designed to be intuitive to use, requiring no specialised software or user expertise. Input is extremely easy and requires the user to highlight the area of interest on a map or using grid co‐ordinates. Output is delivered via the web application and comprises a customised PDF containing the maps and a zip file of geographical information system (GIS) data for the area requested. Users may run an unlimited number of LEFT analyses and download reports free of charge. In addition to the free tool described in this paper, there is also a paid service: individual LEFT analyses can be upgraded for a charge to allow access to the geographically subsetted datasets generated for each report. These data are supplied as a zip file containing raster datasets for the layers in the LEFT analysis in GeoTIFF format. These can be opened and queried in a GIS software package.